Internet-delivered cognitive behavior therapy for anxiety and insomnia in a higher education context. Issue 4 (3rd July 2016) - Morris, Joanna; Firkins, Ashlyn; Millings, Abigail; Mohr, Christine; Redford, Paul; Rowe, Angela
ABSTRACT: Background and Objectives : Anxiety and insomnia can be treated with internet-delivered Cognitive Behavioral Therapy (iCBT). iCBT may be well-suited to students who are known to be poor help-seekers and suffer these symptoms. iCBT can offer easy access to treatment and increase service availability. The aim of this study was to evaluate the efficacy of anxiety and insomnia iCBT programs in students.Design : A randomized, controlled study.Methods : Students were randomly allocated to intervention ("Anxiety Relief": n  = 43; "Insomnia Relief": n  = 48; control: n  = 47). Interventions lasted six weeks. Outcome measures were the State-Trait Anxiety Inventory and the Pittsburgh Sleep Quality Index.Results : Significant within-group reductions in anxiety ( t (31) = 2.00, p  = .03) with moderate between-groups (compared to control) effect size ( d  = .64) and increases in sleep quality ( t (31) = 3.46, p  = .002) with a moderate between-groups effect size ( d  = .55) were found for completers of the anxiety program from pre- to post-intervention. Significant within-group increases in sleep quality were found for completers of the insomnia program from pre- to post-intervention ( t (35) = 4.28, p  > .001) with a moderate between-groups effect size ( d  = .51).Conclusions : Findings support the use of iCBT for anxiety and insomnia in students, and indicate that further research is needed.